2012
DOI: 10.1007/s11033-012-1521-3
|View full text |Cite
|
Sign up to set email alerts
|

A mini review on the antimicrobial peptides isolated from the genus Hylarana (Amphibia: Anura) with a proposed nomenclature for amphibian skin peptides

Abstract: Hylarana is a well established frog genus coming under the family Ranidae. An increasing number of antimicrobial peptides have been isolated and characterized from the skin of frogs of this genus. This review covers the antimicrobial peptides reported so far from the frogs of Hylarana genus and to propose a consistent system of nomenclature for amphibian skin peptides. Multiple sequence alignment of the skin peptides from Hylarana genus has grouped them into six peptide families, and three bioactive peptides. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…To conclude, taking into account the high diversity of shrimp ALFs explored here, we propose a uniform nomenclature for shrimp ALFs, as adopted for other AMP families, such as avian β-defensins [43], amphibian skin peptides [44], and shrimp penaeidins [35]. Like the penaeidin (PEN) nomenclature, the shrimp ALF nomenclature is based on the conserved amino acid residues found in the mature polypeptides of each ALF Group ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, taking into account the high diversity of shrimp ALFs explored here, we propose a uniform nomenclature for shrimp ALFs, as adopted for other AMP families, such as avian β-defensins [43], amphibian skin peptides [44], and shrimp penaeidins [35]. Like the penaeidin (PEN) nomenclature, the shrimp ALF nomenclature is based on the conserved amino acid residues found in the mature polypeptides of each ALF Group ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However they are given different names irrespective of their structural similarity (Fig. 1B) as in the case of Gaegurin and Rugosin, which was renamed later [4]. Lividin 8 HYba identified in the present study showed similarity to Lividins and Odorranains, but on detailed analysis of their sequences and publication dates, it was found that such a sequence first reported was Lividin 8 (GenBank acc.…”
mentioning
confidence: 61%
“…no: ADV36193) and a second encoding Spinulosain precursor with 92% identity to Spinulosain-A1 from Hylarana spinulosa [7]. The new peptides were named according to the recently accepted nomenclature system [4] and submitted to GenBank (GenBank acc. nos: KR995268, KR995269).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NCBI BLAST search revealed that both the peptides showed 67% similarity with brevinin1 SN1 from Sylvirana spinulosa . The peptides were named as brevinin1 HYba1 and brevinin1 HYba2, respectively, according to the proposed nomenclature system for frog skin peptides.…”
Section: Resultsmentioning
confidence: 99%